DAMPAK KINERJA DAN LEVEL ETIKA TERHADAP KETERBACAAN PENGUNGKAPAN - Munandar, Agus (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2018)
This Research aims to investigate the reporting mechanism based on its financial performance and ethics. This research using experimental methods for confirming these findings, and considers ethics level as a moderating effect on its opportunist motivation of managers. The findings of this research show that performance affects the readability of disclosures. It consistent with previous findings. Beside that, this research also indicates that ethics have an impact on disclosure readability. Then, ethics can marginally moderate relationshipfinancial performance and disclosure readability. Keywords: Readibility, Performance, Experimental methods